The Accuracy Comparison of Oscilloscope and Voltmeter Utilizated in Getting Dielectric Constant Values - Bowo Eko Cahyono; Misto Misto; Rofiatun Rofiatun (UNEJ e-Proceeding, 2016)
Parallel plate capacitor is widely used as a sensor for many purposes. Researches which have used parallel plate capacitor were investigation of dielectric properties of soil in various temperature [1], characterization if cement’s dielectric [2], and measuring the dielectric constant of material in various thickness [3]. In the investigation the changing of dielectric constant, indirect method can be applied to get the dielectric constant number by measuring the voltage of input and output of the utilized circuit [4]. Oscilloscope is able to measure the voltage value although the common tool for that measurement is voltmeter. This research aims to investigate the accuracy of voltage measurement by using oscilloscope and voltmeter which leads to the accuracy of values of dielectric constant. The experiment is carried out by an electric circuit consisting of ceramic capacitor and sensor of parallel plate capacitor, function generator as a current source, oscilloscope, and voltmeters. Sensor of parallel plate capacitor is filled up with cooking oil in various concentrations, and the output voltage of the circuit is measured by using oscilloscope and also voltmeter as well. The resulted voltage values are then applied to the equation to get dielectric constant values. Finally the plot is made for dielectric constant values along the changing of cooking oil concentration. The results show that the plot of dielectric constant values which are gained from the voltage measurement using voltmeter have better linearity compare to the other plot in which the voltage measurement utilize the oscilloscope. In conclusion, voltmeter is considered better equipment to measure a voltage compare to the oscilloscope in term of getting dielectric constant values of parallel plate capacitance sensor.